2020
DOI: 10.1002/mcf2.10105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Population Recovery Characteristics and Potential Recovery Actions for a Long‐Lived Protected Species: A Case History of Gulf Sturgeon in the Apalachicola River

Abstract: In the U.S. Gulf of Mexico, Gulf Sturgeon Acipenser oxyrinchus desotoi supported an intense and short‐lived commercial fishery in the early twentieth century. Thereafter, it persisted at very low levels until the fishery was closed by individual U.S. states in the Gulf of Mexico region in the mid‐1980s. Despite the closure of the fishery, the stock has not recovered and there have been threats to population recovery including the potential effects of the Deepwater Horizon oil spill, storm events, and harmful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…Although they do not constitute a regular pressure faced by Gulf Sturgeon, stochastic mass mortality events can affect abundance recovery timelines. Gulf Sturgeon populations are inherently slow growing because of their late age of maturity and intermittent spawning periodicity, and they are generally sensitive to increases in adult mortality (Rudd et al 2014; Flowers et al 2020). Pine et al (2001) estimated a growth rate of only about 5% per year for the Suwannee River population during its recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…Although they do not constitute a regular pressure faced by Gulf Sturgeon, stochastic mass mortality events can affect abundance recovery timelines. Gulf Sturgeon populations are inherently slow growing because of their late age of maturity and intermittent spawning periodicity, and they are generally sensitive to increases in adult mortality (Rudd et al 2014; Flowers et al 2020). Pine et al (2001) estimated a growth rate of only about 5% per year for the Suwannee River population during its recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…After months of fasting throughout the summer, adult Gulf sturgeon must outmigrate to marine waters to restore their energy by foraging on the rich benthic resources present in these areas (Sulak et al., 2016). Population modeling has indicated that Gulf sturgeon population growth is highly sensitive to increases in adult mortality rates (Flowers et al., 2020; Rudd et al., 2014), thus the costs and benefits of continuing Gulf sturgeon passage in this system – and involving both males and females – must be carefully considered (George et al., 2009), perhaps by way of theoretical modeling before further experimentation (Jager, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are 7 reproducing populations of Gulf sturgeon, although a few more existed historically. Dams in the Mobile and Ochlockonee river systems are thought to have led to the extirpation of resident populations (Sulak et al., 2016), whereas other systems like the Apalachicola River still support a remnant population decades after the species was granted federal protections under the Endangered Species Act in 1991 (Flowers et al., 2020).…”
Section: Introductionmentioning
confidence: 99%